Обоснование расчетных схем замещения асинхронных двигателей - Родькин, Д.И.; Ромашихин, Ю.В. (Технічна електродинаміка, 2012)
The existing defects in induction motors. Determined by the equivalent circuit to describe the physical processes in induction motors, taking into account the existing defects. The choice of the equivalent circuits of diagnostic features in the analysis of the stator voltages and currents, as well as components of the instantaneous power and its harmonic content. The efficiency of the energy method for identification of the electromagnetic parameters of induction motors, taking into account the existing defects.